A comprehensive review on the removal of noxious pollutants using carrageenan based advanced adsorbents. (February 2022) - Sharma, Gaurav; Khosla, Atul; Kumar, Amit; Kaushal, Nikhil; Sharma, Shweta; Naushad, M.; Vo, Dai-Viet N.; Iqbal, Jibran; Stadler, Florian J.
Abstract: Rapid industrial development is associated with high discharge of toxic pollutants into the environment. The industries discharge their wastewater containing organic pollutants directly into the water system without treating them that has posed many serious threats to environmental protection. The use of bioadsorbents for the removal of such toxic pollutants from the waste water due to its simple synthesis, easy operation, effectiveness, and economic viability have emerged a new dimension in the wastewater treatment approaches. Various adsorbents have been prepared to examine their adsorption capacity against different adsorbates, but, to attain sustainability, biocompatibility, and biodegradation, bio-adsorbents have been found to won the battle. Seaweed derived polysaccharide; Carrageenan (CR) has been proven to be an excellent adsorbent for the wastewater treatment. It has been successfully modified with various components to form CR based-magnetic composites, hydrogels, nanoparticle modified CR composites and many others to enrich and diversify its properties. In this review, we have explained the adsorption behaviour of various carrageenan based adsorbents for the removal of different dyes. The influence of various parameters such as the effect of initial concentration, adsorbent dosage, contact time, pH, temperature, and ion concentration on dye adsorption is well explained. This paper also summarizes the structure, morphology, swelling ability, and thermal stability of carrageenan. The data also expounds on the adsorption capacity, kinetic model, isotherm model, and nature of the adsorption process. Different types of solvents are used for the regeneration and reusability of carrageenan adsorbents and their regeneration studies and desorption efficiency is well-explained. The adsorption mechanism of dyes onto carrageenan based adsorbents has been well described in this review. This review provides a deep insight about the use of carrageenan based adsorbents for the wastewater treatment. Graphical abstract: Image 1 Highlights: A comprehensive review based on carrageenan or its various composites. Carrageenan based adsorbents for removal of numerous pollutants were surveyed. Various influential factors on the adsorption was taken into consideration. Various categories of carrageenan were studied.